The Effect of Production Input and Efficiency of Rice Farming in Padangguni District, Konawe Regency - Syarbiah, Sarty; Sukratman, I Made (CV. Media Digital Publikasi Indonesia, 2024)
The purpose of this study was to determine the production input and input price efficiency in rice farming in Padangguni District, Konawe Regency. The determination of the location of this study was carried out considering that in this place almost all the people are engaged in rice farming. The sample in this study was taken using a simple random sampling method with a sample size of 100 respondents. To determine the effect of the use of production inputs in rice farming in Padangguni District, Konawe Regency, regression analysis and price efficiency were used. The production factors used in the form of land, labor, seeds, fertilizers and pesticides have a significant effect on the production of rice farming in Langgea Village, Padangguni District, Konawe Regency. This shows that these production factors complement each other and are very much needed to increase the productivity of rice farming. The combination of the use of production factors for rice farming in Langgea Village, Padangguni District, Konawe Regency is not yet efficient. This is indicated by the efficiency value of each production factor which is not equal to one (NPMxi / Pxi ≠ 1), namely; land rental efficiency value (0.94), labor (0.30), seeds (1.77) fertilizer (0.77) and pesticides (0.69). This means that the combination of the use of production factors for rice farming is still inefficient.